1999
DOI: 10.1557/s109257830000346x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Controlling of Strain During MOCVD of AlGaN for UV Optoelectronics

Abstract: The grown-in tensile strain, due to a lattice mismatch between AlGaN and GaN, is responsible for the observed cracking that seriously limits the feasibility of nitride-based ultraviolet (UV) emitters. We report in-situ monitoring of strain/stress during MOCVD of AlGaN based on a wafer-curvature measurement technique. The strain/stress measurement confirms the presence of tensile strain during growth of AlGaN pseudomorphically on a thick GaN layer. Further growth leads to the onset of stress relief through crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
(16 reference statements)
1
24
0
Order By: Relevance
“…2 We have shown that relaxation of tensilely stressed AIGaN (on GaN) proceeds through the propagation of incipient cracks, which in turn activates the slip systems for misfit dislocations around the crack tips.3 Even though III-nitride devices are known for their relative insensitivity to a high density of dislocations,4 cracking due to the tensile mismatch between AIGaN and the GaN pseudo-substrate tends to severely deteriorate device performance. 5 Various types of intdayers, generally referred to as a low-temperature (LT) grown layer inserted between two layers grown at regular, high temperatures (HT), have been reported to influence the structural properties of the III-Nitrides. Table I.…”
Section: Most Of the Iii-nitride Devices To Date Have Been Grown On Tmentioning
confidence: 99%
“…2 We have shown that relaxation of tensilely stressed AIGaN (on GaN) proceeds through the propagation of incipient cracks, which in turn activates the slip systems for misfit dislocations around the crack tips.3 Even though III-nitride devices are known for their relative insensitivity to a high density of dislocations,4 cracking due to the tensile mismatch between AIGaN and the GaN pseudo-substrate tends to severely deteriorate device performance. 5 Various types of intdayers, generally referred to as a low-temperature (LT) grown layer inserted between two layers grown at regular, high temperatures (HT), have been reported to influence the structural properties of the III-Nitrides. Table I.…”
Section: Most Of the Iii-nitride Devices To Date Have Been Grown On Tmentioning
confidence: 99%
“…At the initial stage of the growth, HT-GaN is under compressive stress. After growing HT-GaN less than one micron thick, it changes to tensile stress [13]. This process is repeated during the series of the LT-interlayer/HT growth, therefore the final stress is the same for all the GaN layers.…”
Section: Process Of Gan Growth On a Low-temperature Interlayermentioning
confidence: 99%
“…The concern was reiterated by Peng et al [63] in stating, based on optical absorption measurements of sputtered polycrystalline films, that AlInN and AlGaInN do not seem to provide good confinement (to GaInN) due to a very strong bowing effect. We have shown from in-situ stress measurement that the use of high Al-fraction (or thick) AlGaN barriers on GaN templates, required for electrical and optical confinement in UV devices, leads to a buildup of tensile stress and subsequently the occurrence of cracking [44]. As discussed in this section, introducing indium into GaN greatly enhances the optical efficiency but at the cost of an increase in emission wavelength.…”
Section: Mocvd Growth Of Quaternary (Algain)n For Uv Optoelectronicsmentioning
confidence: 88%
“…Furthermore, mismatch-induced tensile stress was observed during growth of AlGaN heterostructures on thick GaN templates for UV devices [44], leading to relaxation through crack generation. Quaternary AlGaInN compound semiconductors are expected to enclose a finite (non-zero) area on the plot of energy gap versus lattice constant.…”
Section: Mocvd Growth Of Quaternary (Algain)n For Uv Optoelectronicsmentioning
confidence: 99%